In vitro starch digestibility of bread with banana (Musa acuminata X balbisiana ABB cv. Awak) pseudo-stem flour and hydrocolloids - Ho, Lee-Hoon; Thuan-Chew, Tan; Noor Aziah, Abdul Aziz (Elsevier Ltd., 2015)
Novel composite breads were prepared by using banana pseudo-stem flour (BPF). BPF was substituted for commercial wheat flour (CWF) (at 10%, w/w) to prepare B10BPF and the B10BPF with added hydrocolloids [xanthan gum (XG) or sodium carboxy-methyl cellulose (Na CMC)] to prepare B10BPFXG and B10BPFCMC, respectively. The prepared composite breads had high level of minerals (calcium, phosphorus, potassium, magnesium, iron, and manganese), total sugars, and resistant starch contents. Except for the composite bread prepared by adding XG, all other samples showed non-significant decrease in the total and digestible starch. Slow starch hydrolysis rate (corresponding to increase in time) was recorded with a subsequent reduction of hydrolysis index and estimated glycemic index in the composite breads. As this is a novel composite bread developed with health promoting properties, it is expected to benefit consumers, especially for those requiring high fiber diets.